DIGITALIZATION IN THE FOCUS OF CONTEMPORARY CULTURE AND ART: A PHILOSOPHICAL AND CULTURAL STUDIES PERSPECTIVE - Melnychuk, Maksym; Sokolovskyi, Oleh (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Introduction. The article analyzes the transformation of originality and authorship in art under conditions of digitalization. Particular attention is paid to changes in the ontological status of the artwork in immersive and interactive digital environments. The aim and tasks. The aim of the article is to analyze the transformation of the ontological status of the original artwork, to examine the critical potential of Walter Benjamin’s concept of the “aura” in the context of digital art, and to identify new forms of viewer-artwork interaction in immersive digital environments. Research methods. The research methodology combines hermeneutic analysis, comparative method, and case study analysis based on the TeamLab Borderless museum (Japan). The theoretical framework includes Walter Benjamin’s concept of the “aura,” Jean Baudrillard’s theory of simulacra, and Paul Virilio’s analysis of the crisis of perception. Research results. The study demonstrates that under conditions of digital reproduction the value of an artwork shifts from the uniqueness of the physical object to the uniqueness of the concept and interaction process. In immersive digital art, the viewer becomes a participant in the artistic event rather than a passive observer. The analysis of TeamLab Borderless confirms that each interaction with a digital installation acquires a unique processual character, even when the technical basis of the artwork remains unchanged. At the same time, digital artworks reveal ontological vulnerability because their existence depends entirely on technological infrastructure. Discussion. The obtained results make it possible to reconsider Benjamin’s concept of the “aura” in the context of digital culture. Unlike approaches that interpret digital reproduction exclusively as the loss of authenticity, the study argues that uniqueness increasingly manifests itself through interactive and processual forms of artistic experience. These conclusions partly confirm and extend Baudrillard’s interpretation of simulation in contemporary culture. Conclusions. Contemporary digital art transforms traditional concepts of originality, authorship, and artistic presence. In immersive environments, the uniqueness of the artwork is increasingly connected not with material singularity but with the unrepeatable character of interaction. This creates the need for new philosophical and cultural criteria capable of distinguishing artistic communication from simulacral forms of digital reproduction.